The effect of single- and multiple-dose etravirine on a drug cocktail of representative cytochrome P450 probes and digoxin in healthy subjects - Kakuda, Thomas N; Van Solingen-Ristea, Rodica M; Onkelinx, Joelle; Stevens, Tanja; Aharchi, Fatima; De Smedt, Goedele; Peeters, Monika; Leopold, Lorant; Hoetelmans, Richard M W (Journal of clinical pharmacology, 2014)
The effect of etravirine on cytochrome P450 (CYP) enzymes and P-glycoprotein were evaluated in two randomized, crossover trials in healthy subjects. A modified Cooperstown 5 + 1 cocktail was utilized to determine the effects of etravirine on single-dose pharmacokinetics of model CYP probes. The cocktail was administered alone, then, after a 14-day washout, etravirine 200 mg twice daily (bid) was given for 14 days with cocktail on days 1 and 14. In a separate study, digoxin (0.5 mg) was administered alone, then, after a 14-day washout, etravirine 200 mg bid was administered for 12 days with digoxin on day 8. In the cocktail study, the AUClast least squares mean (LSM) ratios (90% confidence intervals [CIs]) for cocktail + etravirine versus cocktail were 0.93 (0.88, 0.99; paraxanthine), 0.58 (0.44, 0.75; 7-OH-S-warfarin), 0.43 (0.20, 0.96; 5-OH-omeprazole), 0.85 (0.78, 0.94; dextrorphan), and 0.69 (0.64, 0.74; midazolam). Digoxin AUC0-8h was slightly increased with etravirine coadministration (LSM ratio 1.18 [0.90, 1.56]). These data suggest that etravirine is a weak CYP3A isozyme inducer and minimally inhibits CYP2C9, 2C19, and P-glycoprotein activity.